What's interpersonal in interpersonal perception? The role of target's attachment in the accuracy of perception. Issue 4 (9th October 2017) - Sadikaj, Gentiana; Moskowitz, D. S.; Zuroff, David C.
Abstract: Objective: We examined the influence of attachment orientation on the accuracy of perception of negative affect in close relationships. We hypothesized that tracking accuracy of perceiving negative affect (a) would be lower among perceivers and targets with higher attachment avoidance and (b) would be lowest when both the target and perceiver were high on attachment avoidance. Tracking accuracy would be (c) higher among perceivers and targets with higher attachment anxiety and (d) highest when both the target and perceiver were high on attachment anxiety. Method: We collected data from 92 couples who reported their negative affect and perception of their partner's negative affect in interactions with each other on 20 days. Results: Results supported the hypotheses for attachment avoidance and tracking accuracy. Tracking accuracy of perceived negative affect was low when the target was high on attachment avoidance; accuracy was lowest when both the target and the perceiver were high on attachment avoidance. Conclusions: Lower "readability" of high avoidantly attached targets' emotions may inhibit intimacy and sensitive responding, which thereby may contribute to poor relationship outcomes.